PENGARUH KOMUNIKASI DAN KECERDASAN EMOSIONAL TERHADAP KINERJA PEGAWAI PADA DINAS REGISTRASI KEPENDUDUKAN ACEH - Farah Ivana; Yusni Hervy (SI-MEN, 2021)
The purpose of study was to determine effect of Communication and Emotional Intelligence on Employee Performance at the Aceh Population Registration Service, either partially or simultaneously. The research data collection method was analyzed using multiple linear regression models and processed using the SPSS (Statistical Product and Service Solution). The number of samples in study were 52 respondents. Research data were collected through questionnaires, and documentation studies. Hypothesis testing using multiple linear regression analysis, F test and t test is intended to determine simultaneously and partially the effect of the independent variable on the dependent variable at the 95% confidence level (α = 0.05). The results of the study based on the simultaneous test showed that the variables of Communication and Emotional Intelligence had a significant effect on Employee Performance at the Aceh Population Registration Service. The partial test also shows that the communication variable has a significant effect on employee performance at the Aceh Population Registration Service. Then Emotional Intelligence has a significant effect on Employee Performance at the Aceh Population Registration Service. The conclusion of study communications significantly influence the performance of employees at the Department of Population Registration Aceh value t count (2.069) is greater than ttable (2,010). Emotional intelligence significantly influence the performance of employees at the Department of Population Registration Aceh value t (10.231) is more than the value of ttable (2,010). communication and emotional intelligence simultaneously affect the performance of employees at the Aceh Population Registration Service with F value Fcount (65,608) is greater than Ftable (3,187).